Bioprospecting of serratiopeptidase-producing bacteria from different sources - Nair, Sreelakshmi R.; Subathra Devi, C. (Frontiers in Microbiology, 2024)
Anti-inflammatory enzymes have wide applications in the pharmaceutical industry. The objective of this study was to find new and efficient strains for the commercial production of serratiopeptidase enzyme. Vast number of samples were processed for the isolation of potent strains. The experimental treatment includes processing of twenty soil samples, silkworm gut, and sugarcane stem. The total protein and protease activity was estimated by Lowry’s method and casein hydrolysis. The HRBC stabilization assay was performed for finding the anti-inflammatory potential of all strains. The serratiopeptidase production was confirmed by HPLC with the standard. Molecular characterization of selected potent strains was done by 16S rDNA and confirmed the taxonomy. The one step rapid purification of serratiopeptidase was performed by Ultra three phase partitioning method. The clot lysis potential of the Serratia marcescens VS56 was observed by modified Holmstorm method. The results of the study revealed that among the 60 strains, 12 strains were protease-positive on skim milk agar plates and showed significant protease activity. All 12 strains were screened for serratiopeptidase using high-performance liquid chromatography (HPLC) and VS56, VS10, VS12 and VS18 showed a similar retention time (4.66 ± 0.10 min) with standard. The selected potent strain, Serratia marcescens VS56 showed a proteolytic activity of 21.30 units/mL and produced a total protein of 102 mg/mL. The HRBC suspension results also showed a percentage of 94.6 ± 1.00 protection, which was compared to the standard diclofenac. The clot lysis potential of Serratia marcescens VS56 was 53% in 4 h. Furthermore, the molecular weight of the protein was identified to confirm the presence of serratiopeptidase. The study hence contributed successfully to isolating, screening, and identifying a potent producer for serratiopeptidase from an environmental source. This inherent advantage of the strain will undoubtedly contribute much to the coco comm commercial production of serratiopeptidase in the near future.